Influence of Service Quality and Store Atmosphere on Repurchase Intention at Najmia Beauty Cosmetics Store, Ungaran - Jihan Aurlya Candy; Andi Setiawan; Paniya (Admisi dan Bisnis, 2026)
The  study  aims  to  analyze  the  influence  of service  quality,  and  store atmosphere on repurchase intention of Najmia Beauty Ungaran Cosmetic Store. In this study using 100 samples who are customers of Najmia Beauty Ungaran Cosmetic Store, which were obtained through distributing questionnaires using  purposive  sampling  techniques.  The  data  obtained  was  processed  using  multiple  linear regression  analysis  methods  and  SPSS  25  analysis  tools.  This  study  proves  empirically  that  service quality  (X1), and  store  atmosphere  (X2),  have  a  significant  impact  on repurchase intention (Y) of Najmia Beauty Ungaran Cosmetic Store. This study is expected to be a way out on determine  the  right  marketing  strategy  in  facing  market  rivalry  in  the  store beauty   by applying service quality, and store atmosphere to increase repurchase intention on Najmia Beauty Ungaran Cosmetic Store.